2020
DOI: 10.3847/1538-4357/abbdfa
|View full text |Cite
|
Sign up to set email alerts
|

Serendipitous Discovery of Nine White Dwarfs with Gaseous Debris Disks

Abstract: Optical spectroscopic observations of white dwarf stars selected from catalogs based on the Gaia DR2 database reveal nine new gaseous debris disks that orbit single white dwarf stars, about a factor of 2 increase over the previously known sample. For each source we present gas emission lines identified and basic stellar parameters, including abundances for lines seen with low-resolution spectroscopy. Principle discoveries include (1) the coolest white dwarf (T eff ≈ 12,720 K) with a gas disk;… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 91 publications
1
41
0
Order By: Relevance
“…The candidate emission feature detected in the 5169 Å Fe region also changes in morphology between the two epochs, where the red-shifted component of the profile contracts to shorter wavelengths, corresponding to smaller velocities. We note that this region has also been shown to host 5167 Å, 5173 Å, and 5184 Å Mg emission for some gaseous debris discs (see Melis et al 2020;Dennihy et al 2020b;Gentile Fusillo et al 2021). The potential O emission feature appears to share the red-dominated asymmetry of the Ca triplet.…”
Section: Additional Candidate Emission Profilesmentioning
confidence: 59%
See 1 more Smart Citation
“…The candidate emission feature detected in the 5169 Å Fe region also changes in morphology between the two epochs, where the red-shifted component of the profile contracts to shorter wavelengths, corresponding to smaller velocities. We note that this region has also been shown to host 5167 Å, 5173 Å, and 5184 Å Mg emission for some gaseous debris discs (see Melis et al 2020;Dennihy et al 2020b;Gentile Fusillo et al 2021). The potential O emission feature appears to share the red-dominated asymmetry of the Ca triplet.…”
Section: Additional Candidate Emission Profilesmentioning
confidence: 59%
“…If the emission generated by a single planetesimal is proportional in strength to the total emission from the gaseous component of the disc, then it would be more efficient to observe gaseous debris discs with emission features comparable in strength to those at SDSS J1228+1040. Melis et al (2020), Dennihy et al (2020b) and Gentile Fusillo et al ( 2021) recently reported the combined detection of 14 new gaseous debris discs (for a total of 21 gaseous debris disc systems), five of which -SDSS J0006+2858, WD 0347+1624, WD 0611-6931, WD J0846+5703, and WD J2133+2428, show strong Ca triplet emission. Furthermore, the morphology of the emission profiles of WD 0347+1624 appears to vary on a time-scale of 2 -3 yrs; similar to HE 1349-2305 and indicative of the precession of the debris disc.…”
Section: Non-detection Of Short-term Periodic Variationsmentioning
confidence: 99%
“…This rare polluting element is extremely difficult to detect in hotter white dwarfs and could be the signpost of accretion of the crust of a planetary object (Hollands et al 2021). More discoveries related to planetary systems around white dwarfs enabled by Gaia included WD J0914+1914, a peculiar white dwarf in the process of evaporating a Neptune-like exoplanet (Gänsicke et al 2019), and the 14 newly identified white dwarfs with gaseous debris from rocky planetesimals (Dennihy et al 2020;Melis et al 2020;Gentile Fusillo et al 2021), which brought the number of such systems known from seven to 21.…”
mentioning
confidence: 99%
“…In around 21 of the white dwarfs which are host to dusty debris discs we have also observed a gaseous component to the disc (Gänsicke et al 2006(Gänsicke et al , 2007(Gänsicke et al , 2008Gänsicke 2011;Farihi et al 2012;Melis et al 2012;Wilson et al 2014;Dennihy et al 2020;Gentile Fusillo et al 2020;Melis et al 2020). The presence of these discs is inferred through the detection of the double-peaked Ca II emission triplet (∼ 8600 Å) in the spectrum of the system (Horne & Marsh 1986).…”
Section: Introductionmentioning
confidence: 71%